Effects of hexavalent chromium on growth , phytotoxicity , tolerance index of Cosmos bipinnatus, Cav. and Celosia cristata, L. - Phytoremediation - Karthik, K.; Sharavanan, P.S. (Journal of Aridland Agriculture, 2016)
Genetically modified (GM) foods are derived from organisms whose genetic material (DNA) has been modified in a way that does not occur naturally. The introduction of a gene from a different organism or the term genetically modified plants and foods are most commonly used to refer to crop plants created for human and animal consumption using the latest molecular biology techniques. But not all genetically modified plants are grown as crops. There are many genetically modified ornamental plants are used for flowering purpose. The latest molecular technology alters the plant quality and used for many purposes. This present study is to investigate phytoremediation based on genetically modified ornamental plants Cosmos bipinnatus, Cav. and Celosia cristata,L. belongs to Astraceae and Amaranthaceae family.Â  Â The main aim of the study is remedy for heavy metal pollution and relation to human health, ecosystem and economical disasters of wealthy and poor farmers.